An initial investigation of the unique relationship between disgust propensity and body dysmorphic disorder. (November 2018) - Wilver, Natalie L.; Summers, Berta J.; Garratt, Grace H.; Carlton, Corinne N.; Cougle, Jesse R.
Highlights: Explored relationship between disgust propensity and body dysmorphic disorder. Disgust propensity predicted greater self-reported BDD symptoms among a student sample. Disgust propensity predicted greater BDD-related concerns during an in-vivo behavioral task. A clinical BDD group reported greater Disgust propensity relative to healthy controls. Findings were significant after accounting for co-occurring depression and anxiety. Abstract: Disgust is a universal emotion that has received recent empirical attention for its potential role in various forms of psychopathology. We conducted two studies using varying methods to explore the relationship between disgust propensity, a construct related to obsessive-compulsive symptomatology, and symptoms of body dysmorphic disorder (BDD). Study 1 found a significant and unique (i.e., above and beyond co-occurring depression and anxiety) relationship between higher disgust propensity and more severe BDD symptoms, as measured by a standardized self-report and via an in-vivo task aimed at eliciting BDD-related concerns ( N  = 200). In Study 2, a clinical sample of individuals with BDD ( N  = 50) reported higher disgust propensity compared to mentally healthy controls ( N  = 36). This finding remained significant when controlling for depression and anxiety. Findings are the first to our knowledge to demonstrate a relationship between disgust propensity and BDD symptoms and provide directions for future research exploring the role of disgust in BDD.